2021
DOI: 10.3389/fphys.2021.715265
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in Geometry Among Coronary Atherosclerotic Plaques Extracted From Computed Tomography Angiography

Abstract: Background: The three-dimensional (3D) geometry of coronary atherosclerotic plaques is associated with plaque growth and the occurrence of coronary artery disease. However, there is a lack of studies on the 3D geometric properties of coronary plaques. We aim to investigate if coronary plaques of different sizes are consistent in geometric properties.Methods: Nineteen cases with symptomatic stenosis caused by atherosclerotic plaques in the left coronary artery were included. Based on attenuation values on compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Studies have confirmed that the geometry of intracranial artery is an important factor in the development of atherosclerotic plaque 10–12. The arterial geometry, by haemodynamically working on the endothelia, can influence the growth of atherosclerotic plaques through the haemodynamic effect, leading to a consistency in geometry among different plaques 13. Moreover, the geometric properties of plaque can directly influence the risk of plaque rupture 14 15.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies have confirmed that the geometry of intracranial artery is an important factor in the development of atherosclerotic plaque 10–12. The arterial geometry, by haemodynamically working on the endothelia, can influence the growth of atherosclerotic plaques through the haemodynamic effect, leading to a consistency in geometry among different plaques 13. Moreover, the geometric properties of plaque can directly influence the risk of plaque rupture 14 15.…”
Section: Introductionmentioning
confidence: 94%
“…[10][11][12] The arterial geometry, by haemodynamically working on the endothelia, can influence the growth of atherosclerotic plaques through the haemodynamic effect, leading to a consistency in geometry among different plaques. 13 Moreover, the geometric properties of plaque can directly influence the risk of plaque rupture. 14 15 In fact, the plaque features, including geometry, are found to be associated with the acute symptoms in MCA.…”
Section: Introductionmentioning
confidence: 99%
“…The attenuation values on CT corresponds to the different plaque components. Some studies suggested attenuation values not exceeding (150). Yoon et al also showed a positive correlation between the plaque calcification score and degree of stenosis in 66 patients (151).…”
Section: Morphological Parametersmentioning
confidence: 99%
“…Different techniques currently exist for plaque characterization, ranging from non-invasive modalities, such as coronary computer tomography (CT), to intravascular imaging (intravascular ultrasound (IVUS) or optical coherence tomography (OCT)). Advances in coronary CT now allow for plaque geometrical and compositional assumptions [ 5 , 6 ] and it was proven that some of the features identified on CT imaging could correlate with the risk of future clinical events [ 7 ]. Nevertheless, CT interpretation is sometimes cumbersome due to certain factors, such as “the blooming’’ effect and low image resolution.…”
Section: Introductionmentioning
confidence: 99%